Hydrogeochemical Characterization of GeothermalWater in Arjuno-Welirang, East Java, Indonesia - Agung Harijoko; Vanadia Martadiastuti; I Wayan Warmada; Kotaro Yonezu (Journal of Applied Geology, 2018)
Arjuno-Welirang Volcanic Complex (AWVC) is one of geothermal fields whichlocated in East Java province, Indonesia. It belongs to a Quarternary volcanic arc and has potential for development of electricity. The field is situated in a steep volcanic terrain and there are only few geothermal manifestations, i.e., hot springs, fumaroles, solfataras, steaming ground and hydrothermal alteration. This study aims to classify the type and source of geothermal fluid and to estimate the reservoir condition of Arjuno- Welirang geothermal system. Data are obtained from collecting water samples including hot springs, cold springs, river waters and rain water, then they are analyzed using ICP-AES, titration and ion chromatography.All thermal waters have temperatures from 39.5–53°C and weakly acidic pH (5.2–6.5). Cangar and Padusanhot springs show bicarbonate water, formed by steam condensing or groundwater mixing. On the other hand, Songgoriti shows Cl-HCO3 type, formed by dilution of chloride fluid by either groundwater or bicarbonate water during lateral flow. All of the waters represent immature waters, indicating no strong outflow of neutral Cl-rich deep waters in AWVC. Cl/B ratios show that all water samples have a similar mixing ratio, showing they are from common fluid sources. However, Padusan and Songgoriti have higher Cl/B ratios than Cangar, suggesting that geothermal fluids possibly have reacted with sedimentary rocks before ascending to the surface. All waters were possibly mixed with shallow groundwater and they underwent rock-water reactions at depth before ascending to the surface. An estimated temperatures reservoir calculated using CO2 geothermometer yielded temperatures of 262–263 °C based on collecting of fumarole gas at Mt. Welirang crater. According to their characteristics, Cangar and Padusan are associated with AWVC, while Songgoriti is associated with Mt. Kawi.